An NADH preferring acetoacetyl-CoA reductase is engaged in poly-3-hydroxybutyrate accumulation in Escherichia coli - Olavarria, Karel; Carnet, Alexandre; Van Renselaar, Joachim; Quakkelaar, Caspar; Cabrera, Ricardo; Da Silva, Leonor Guedes; Smids, Aron L.; Andres Villalobos, Pablo; Van Loosdrecht, Mark C. M.; Wahl, Sebastian Aljoscha (Journal of Biotechnology, 2021)
Oxygen supply implies higher production cost and reduction of maximum theoretical yields. Thus, generation of fermentation products is more cost-effective. Aiming to find a key piece for the production of (poly)-3-hydroxybutyrate (PHB) as a fermentation product, here we characterize an acetoacetyl-CoA reductase, isolated from a Candidatus Accumulibacter phosphatis-enriched mixed culture, showing a (kcatNADH/KMNADH)/(kcatNADPH/KMNADPH)>500. Further kinetic analyses indicate that, at physiological concentrations, this enzyme clearly prefers NADH, presenting the strongest NADH preference so far observed among the acetoacetyl-CoA reductases. Structural and kinetic analyses indicate that residues between E37 and P41 have an important role for the observed NADH preference. Moreover, an operon was assembled combining the phaCA genes from Cupriavidus necator and the gene encoding for this NADH-preferring acetoacetyl-CoA reductase. Escherichia coli cells expressing that assembled operon showed continuous accumulation of PHB under oxygen limiting conditions and PHB titer increased when decreasing the specific oxygen consumption rate. Taken together, these results show that it is possible to generate PHB as a fermentation product in E. coli, opening opportunities for further protein/metabolic engineering strategies envisioning a more efficient anaerobic production of PHB.
CRIS-Team Scopus Importer:2022-01-11
Keywords: acetoacetyl-CoA reductase; cofactor specificity; NADH; NADPH; oxygen limitation; Polyhydroxybutyrate